Preparation of PDA-GO/CS composite scaffold and its effects on the biological properties of human dental pulp stem cells - Yaoyao Li; Xinhui Huang; Weihao Fu; Zonghao Zhang; Kuancheng Xiao; Hongbing Lv (BMC, 2024)
Abstract Reduced graphene oxide (rGO) is an graphene oxide (GO) derivative of graphene, which has a large specific surface area and exhibited satisfactory physicochemical characteristics. In this experiment, GO was reduced by PDA to generate PDA-GO complex, and then PDA-GO was combined with Chitosan (CS) to synthesize PDA-GO/CS composite scaffold. PDA-GO was added to CS to improve the degradation rate of CS, and it was hoped that PDA-GO/CS composite scaffolds could be used in bone tissue engineering. Physicochemical and antimicrobial properties of the different composite scaffolds were examined to find the optimal mass fraction. Besides, we examined the scaffold's biocompatibility by Phalloidin staining and Live and Dead fluorescent staining. Finally, we applied ALP staining, RT-qPCR, and Alizarin red S staining to detect the effect of PDA-GO/CS on the osteogenic differentiation of human dental pulp stem cells (hDPSCs). The results showed that PDA-GO composite was successfully prepared and PDA-GO/CS composite scaffold was synthesized by combining PDA-GO with CS. Among them, 0.3%PDA-GO/CS scaffolds improves the antibacterial activity and hydrophilicity of CS, while reducing the degradation rate. In vitro, PDA-GO/CS has superior biocompatibility and enhances the early proliferation, migration and osteogenic differentiation of hDPSCs. In conclusion, PDA-GO/CS is a new scaffold materialsuitable for cell culture and has promising application prospect as scaffold for bone tissue engineering.